4-[(E)-4-Bromobenzylideneamino]-3-methyl-1H-1,2,4-triazole-5(4H)-thione - Fun, Hoong-Kun (International Union of Crystallography, 2008)
In the title molecule, C(10)H(9)BrN(4)S, the dihedral angle between the triazole and benzene rings is 12.32 (19)°. An intramolecular C—H⋯S hydrogen bond generates an S(6) ring motif. In the crystal packing, centrosymmetrically related molecules are linked into a dimer by N—H⋯S hydrogen bonds, and the dimers are linked into a chain running along [1[Image: see text]1] by Br⋯N short contacts [3.187 (3) Å]. The crystal packing is further strengthened by π–π interactions involving the triazole ring [centroid–centroid distance = 3.322 (2) Å].